Factors associated with receiving surgical treatment for menorrhagia in England and Wales: findings from a cohort study of the National Heavy Menstrual Bleeding Audit. Issue 2 (5th February 2019) - Geary, Rebecca Sally; Gurol-Urganci, Ipek; Kiran, Amit; Cromwell, David A; Bansi-Matharu, Loveleen; Shakespeare, Judy; Mahmood, Tahir; van der Meulen, Jan
Abstract : Objective: To examine the factors associated with receiving surgery for heavy menstrual bleeding (HMB) in England and Wales. Design: National cohort study. Setting: National Health Service hospitals. Participants: Women with HMB aged 18–60 who had a new referral to secondary care. Methods: Patient-reported data linked to administrative hospital data. Risk ratios (RR) estimated using multivariable Poisson regression. Primary outcome measure: Surgery within 1 year of first outpatient clinic visit. Results: 14 545 women were included. At their first clinic visit, mean age was 42 years, mean symptom severity score was 62 (scale ranging from 0 (least) to 100 (most severe)), 73.9% of women reported having symptoms for >1 year and 30.4% reported no prior treatment in primary care. One year later, 42.6% had received surgery. Of these, 57.8% had endometrial ablation and 37.2% hysterectomy. Women with more severe symptoms were more likely to have received surgery (most vs least severe quintile, 33.1% vs 56.0%; RR 1.6, 95% CI 1.5 to 1.7). Surgery was more likely among those who reported prior primary care treatment compared with those who did not (48.0% vs 31.1%; RR 1.5, 95% CI 1.4 to 1.6). Surgery was less likely among Asian and more likely among black women, compared with white women. Surgery was not associated with socioeconomic deprivation. Conclusions: Receipt of surgery for HMB depends on symptom severity and prior treatment in primary care. Referral pathways should be locally audited to ensure women with HMB receive care that addresses their individual needs and preferences, especially for those who do not receive treatment in primary care.